AB0980 Is Inflammation (Power Doppler Signal) Associated to the Development of New Bone Erosions in Hand Osteoarthritis? A Longitudinal Ultrasound Study. (10th June 2014) - Mancarella, L.; Addimanda, O.; Pelotti, P.; Pignotti, E.; Pulsatelli, L.; Meliconi, R.
Abstract : Background: Ultrasound (US) detected power Doppler signal (PDS) is frequently observed in erosive hand osteoarthritis (EHOA). So far all studies on US detected synovitis and structural damage in HOA have been cross sectional studies (1). Therefore not able to evaluate the time association between synovitis (PDS) and bone erosions along the lines of what has already been soundly demonstrated in patients with RA both at patient and joint levels. Objectives: We performed a longitudinal study to evaluate the relationship between PDS at basal evaluation and new bone erosions detected after about 4 years in joints of patients with HOA. Methods: In the first evaluation (2), we studied 35 subjects (10 normal controls, 12 with non-EHOA and 13 with EHOA). After a mean of 3.9 years, we performed an X-ray and US re-evaluation of both hands of 32 of the original 35 patients (3 subjects were lost at follow up). We evaluated the time relationship between the presence of PDS at the first study (Time 0: T0) and the development of new bone erosions in the second examination (Time 1: T1). Therefore we took into consideration only the joints which were without bone erosions at baseline and we considered the percentage of the newly detected erosions: radiographic central and marginal erosions, US detected erosions. We performed statistical analysis by General linear model and univariate analysis corrected for patient, age, sex and BMI. Results: We found a significant increase in the percentages of all types of erosions comparing the first and the second imaging evaluation (data not shown). We found that the presence of PDS was significantly associated with a higher prevalence of new central erosions only in proximal interphalangeal (PIP) joints (Table 1 ). In addition, the presence of PDS was associated with new US detected erosions only in distal interphalangeal (DIP) joints (Table 2 ). No association between PDS and the development of new radiographic marginal erosions was observed. Conclusions: Our study demonstrates only partial association between the presence of active synovitis, as detected by PDS, and the subsequent development on new bone erosions. References: Kortekaas MC et al. In erosive hand osteoarthritis more inflammatory signs on ultrasound are found than in the rest of hand osteoarthritis. Ann Rheum Dis. 2013 Jun;72(6):930-4. Mancarella L et al. Ultrasound-detected synovitis with power Doppler signal is associated with severe radiographic damage and reduced cartilage thickness in hand osteoarthritis. Osteoarthritis Cartilage. 2010 Oct;18(10):1263-8. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4928